The role of public-private partnerships in promoting smallholder access to livestock markets in developing countries: Methodology and case studies - Rich, Karl M.; Narrod, Clare A. (International Food Policy Research Institute, 2010)
Rising demands for quality and safety measures in high-value agriculture and livestock markets have necessitated the creation of increasingly complex supply chains to manage the flow of goods and information among channel actors. Public-private partnerships (PPPs) can play a key role in strengthening links within the supply chain, particularly where market failures impede access by the poor. This paper examines the potential of PPPs in promoting smallholder access to such supply chains. A conceptual model is presented that highlights the need to generate chain-level benefits for all channel participants in order for PPPs to be sustainable and to adequately address market failures. A case of both a successful and a failed PPP in livestock markets illustrates the utility of this model.